Comparison between histochemical and immunohistochemical methods for diagnosis of sporotrichosis - Marques, Mariângela Esther Alencar [UNESP]; Coelho, Kunie Iabuki Rabello [UNESP]; Sotto, M. N. [UNESP]; Bacchi, C. E. [UNESP] (BMJ, 1992)
Aims: To compare the efficacy of histochemical and immunohistochemical methods in detecting forms of Sporothrix schenckii in tissue. Methods: Thirty five cutaneous biopsy specimens from 27 patients with sporotrichosis were stained by histochemical haemotoxylin and eosin, periodic acid Schiff, and Gomori's methenamine silver methods and an immunohistochemical (avidin-biotin complex immunoperoxidase) (ABC) technique associated with a newly produced rabbit polyclonal antibody anti-Sporothrix schenckii. Results: A total of 29 (83%) cases were positive by the ABC method used in association with anti-Sporothrix schenckii rabbit polyclonal antibodies. Histochemical methods, using silver staining, periodic acid Schiff, and conventional haematoxylin and eosin detected 37%, 23%, and 23% of forms of S schenckii, respectively. The ABC technique was significantly more reliable than periodic acid Schiff and silver staining techniques. Conclusions: It is concluded that immunostaining is an easy and rapid method which can efficiently increase the accuracy of the diagnosis of sporotrichosis in human tissue.
Keywords: histochemistry; human tissue; immunohistochemistry; skin biopsy; sporotrichosis; Antibodies, Fungal; Histocytochemistry; Immunohistochemistry; Sensitivity and Specificity; Sporothrix; Sporotrichosis